Economia circular na engenharia civil: a influência de rejeitos de louça sanitária na fabricação de concretos - Silva, Eduardo Melo De Andrade (2021)
The civil construction sector is one of the most relevant areas in the economic scope for Brazil because this area has the capacity to raise the rate of employees and thereby improve the population's income and the circulation of the currency in the country. Concrete is the most relevant product in this sector, as it can be used for both structural and non-structural purposes and is - with the exception of water - the most used product in the world. Its manufacture is considerably simple compared to other materials, and it is made by mixing only four elements: cement, fine aggregate, coarse aggregate (normally used sand and gravel, respectively) and water. Regarding solid waste, these are present in absolutely all sectors and, for this reason, the interest to develop a study that can cover the replacement of basic constituents in concrete structure with some input that would be discarded in nature. The aim of this work was to study the impact of replacing gravel from common concretes with sanitary wastes (as coarse aggregate), understanding the nuances of this substitute raw material. Specimens were produced in various formulations and from several predefined periods (3, 7 and 28 days), following the current technical standards. It started with the reference concrete (CR), with 100% of gravel in its composition and replacing, with each new formulation, 25% of the gravel with sanitary wastes (C25, C50, C75 and C100), resulting in a total of 90 samples. Analyzing concrete in its fresh state, all the formulations proved to be workable and with no apparent segregation between the constituents, something essential for its use. The study of concrete in the hardened state, more specifically its resistance to compression, demonstrated that all traces can be used in structural applications. The best result of the compression test after 28 days was the total replacement of the gravel by sanitary ware (reaching a characteristic resistance of approximately 36MPa), followed by the C75 (35MPa) and surpassing the performance of the concrete reference (34MPa). The porosity, according to the tests, decreased as the gravel was replaced by the waste of sanitary ware, with the exception of C25, which was more absorbent to water and this may have resulted in worse mechanical resistance (28MPa). With microscopy analyzes, both optical and scanning electronics were possible to detect more specific characteristics in relation to the arrangement of the structure compounds and anchoring of coarse aggregates in the cementitious matrix (cement paste - aggregate interface). Regarding the anchoring of coarse aggregates in the cementitious matrix, the greater fixation of the natural aggregate (gravel 0) in comparison with the recycled aggregate (sanitary wastes) was notorious. The first proved to be more wrapped in the cement paste as a whole and, the second only as a neighborhood - without a strong relationship in this interface of concrete constituent elements.